2009
DOI: 10.5858/133.5.787
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes for “Suspicious” Category in Thyroid Fine-Needle Aspiration Biopsy: Patient's Sex and Nodule Size Are Possible Predictors of Malignancy

Abstract: Context.—Fine-needle aspiration (FNA) is recommended as an initial screening tool for the diagnosis of thyroid nodules. Approximately 10% of thyroid FNA diagnoses are “suspicious for neoplasm,” warranting surgical resection. Objectives.—To examine the role of a patient's age, sex, size of nodule, and morphologic features as possible predictors of malignancy in patients with cytologic diagnosis of “suspicious for neoplasm.” Design.—Cytopathology slides and reports of 402 consecutiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(20 citation statements)
references
References 12 publications
0
19
1
Order By: Relevance
“…Many clinical risk factors, such as male gender, younger age, large nodule size, and single nodule, have long been recognized as predictors of malignancy in patients with thyroid nodules [49][50][51]. When we investigated such clinical variables as risk factors for cancer, we found no such difference regarding age, sex and nodule number.…”
Section: Discussionmentioning
confidence: 69%
“…Many clinical risk factors, such as male gender, younger age, large nodule size, and single nodule, have long been recognized as predictors of malignancy in patients with thyroid nodules [49][50][51]. When we investigated such clinical variables as risk factors for cancer, we found no such difference regarding age, sex and nodule number.…”
Section: Discussionmentioning
confidence: 69%
“…9,12 On the contrary, this study and others found that the age of the patients was not a predictor of malignancy. 10,16 Malignant tumors were more frequent in male patients than in female patients. 5,10,12 However, tumor size, which may correlate with the risk of malignancy, has been a subject of controversy.…”
Section: Discussionmentioning
confidence: 99%
“…10,16 Malignant tumors were more frequent in male patients than in female patients. 5,10,12 However, tumor size, which may correlate with the risk of malignancy, has been a subject of controversy. Risk of malignancy was higher in nodules measuring 2 cm or larger.…”
Section: Discussionmentioning
confidence: 99%
“…Table 5 The tumor-volume doubling rate (TV-DR) in 667 patients who were followed without surgery for >10 years TV-DR (/year) >0. separate criterion for recommending surgical therapy or determining the extent of thyroidectomy is controversial [2,4,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Several surgical series have reported higher malignancy rates in nodules >3-4 cm, but these studies suffered from both selection bias and potential sampling error [19,33].…”
Section: Discussionmentioning
confidence: 99%